Strategi Manajemen Sumber Daya Manusia Dalam Peningkatan Mutu Pendidikan Di SMA Negeri 1 Gamping - kusuma, dimas hendra (Edugama: Jurnal Kependidikan dan Sosial Keagamaan, 2022)
Abstract With existence management source power man Becomes very important and main because success in education based on on usage source power man that is head school and teacher, so that quality which generated have standard education quality and quality . At SMA Negeri 1 Gamping existence teacher still not yet maximum and effective in enhancement quality education , because existence imbalance leveled education on Thing this that is placement educator and power education which not enough in accordance with his profession . It cause lack of source power man that is teacher. Though there is factors blocker planning source power man at SMA Negeri 1 Gamping like lack of Source power man , facility not enough adequate , discipline as well as work same in doing program and activity which has made . however because existence commitment which strong from head school for doing planning HR, as well as existence spirit which tall from tall from Head School , student , and guardian marid so that until moment this planning source power man for increase quality education at SMA Negeri 1 Gamping still could done with good , although still need upgraded . In the study this goal for study and find planning source power man in enhancement quality at SMA Negeri 1 Gamping , and factor which influence planning source power man at SMA Negeri 1 Gamping as well as study and find problem and obstacle in planning source power man at SMA Negeri 1 Gamping as well as find solution from problem and obstacle the knowing is source power man who there is at school already maximum and effective for increase quality education . Keywords: human resources, principals, quality of education, graduate quality dan planning.